Current Status and Potential Therapeutic Strategies for Using Non-coding RNA to Treat Diabetic Cardiomyopathy - Rai, Amit K.; Lee, Brooke; Gomez, Ramesh; Rajendran, Deepu; Khan, Mahmood; Garikipati, Venkata Naga Srikanth (Frontiers in Physiology, 2021)
Diabetic cardiomyopathy (DCM) is a leading cause of mortality and morbidity among the diabetic patients. DCM is characterized by an increase in oxidative stress with systemic inflammation that leads to cardiac fibrosis, ultimately causing diastolic and systolic dysfunction. Even though the pathophysiology of DCM is well studied, the approach to limit this condition is not met with success. This highlights the need for more knowledge on underlying mechanisms, and innovative therapies. In this regard, emerging evidences suggest a potential role of non-coding RNAs (ncRNAs) including micro-RNAs (miRNAs), long non coding RNAs (lncRNAs) and circular RNAs (circRNAs) as novel diagnostics, mechanisms and therapeutics in the context of DCM. However, our understanding on the role of aforementioned ncRNAs (lncRNAs and circRNAs) in diabetic heart disease is still in its infancy. This review provides a comprehensive update on preclinical and clinical studies that might provide a direction for the development of therapeutic strategies to limit/prevent DCM.